Rekayasa Perangkat Lunak Berbasis Android Sebagai Media Informasi Akademik Siswa SMK PKP 2 Jakarta - Forkas Tiroy Santos Butarbutar; Tria Hadi Kusmato; Ari Irawan` (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2017)
In the context of human resource development education is a business that is consciously directed to develop the potential of young people to have the ability, skills, attitude and personality. Information services in education that can be directly accessed by students will certainly have a very positive impact for educational institutions in the midst of intense competition. The problem of limited access to academic information systems that require users to become statically accessed by the Internet causes the need to design an academic information system application that is able to meet the flexibility needs of the users to be able to access more easily and quickly, in this case through a smartphone device that is currently very widely used because of its fairly affordable price and service facilities are quite promising. Aware of all that, an initiative to actively participate in building an application based information system based on android mobile in SMK PKP 2 Jakarta in informing academic students. It is expected that the information system can be accessed anytime and anywhere. Applications can be used by students to view payment information, student grades and student attendance, student profiles and students extracurricular activities. Methods Research and Development and Waterfall Model is a method used to develop software in this research.